Penggunaan Smartphone dalam Pembelajaran Akhlak Peserta Didik - Ludfi, Achmad Rizal (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
The use of smartphones by elementary school students is increasingly concerning. The importance of moral learning is expected to overcome Alpha generation students, who are born with the knowledge of intelligent devices. This research analyzes the use of smartphones in the moral learning of students at MI Hidayatul Muta'alimin Kediri City. At the same time, this qualitative research uses a descriptive approach. The data collection techniques used in this study are observation, interview, and documentation. This study uses the theory of generation and the opinions of the first scholar. The results of research conducted at MI Hidayatul Muta'alimin show that most students at MI Hidayatul Muta'alimin have the characteristics of the alpha generation. Moral learning for students at Madrasah Ibtida'iyah includes integrating moral development that has been formulated into all subjects, daily activities at school and programmed or planned activities. The implications of using smartphones in moral learning for students' support needs in the pandemic era. Still, they are no longer used in the offline learning era because they affect the mindset of students in terms of learning concentration and morals.